The Influence of Family Economic Education, Lifestyle, Social Media Addiction on Consumptive Behavior Through Economic Literacy - Novanda, Aninditha Putri; Prakoso, Albrian Fiky (Sumber Belajar Sejahtera, 2024)
The purpose of this study is to examine the direct and indirect effects of family economic education, lifestyle, social media addiction, and economic literacy characteristics on consumer behavior. This study takes a quantitative method, similar to explanatory research. The data analysis technique used is SEM, using primary data obtained from respondents through questionnaires from the business manager of Muhammadiyah High School 2 Surabaya. Sampling technique uses probability sampling techniques by applying simple random samplings. The population of this study is the entire student class X of Muhammadiyah High School 2 Surabaya who totaled 369 people. The sample in this study amounted to 192 respondents who consisted of some students of X class Muhammadiyah high school 2 Surabaya. The results of this study show that there is a positive and significant influence of family economic education on the economic literacy of pupils of classes X of Muhammadiyah High School 2 Surabaya. There is a negative and non-significant influence on the consumptive behavior of pupiles of classes x of Muhammadiah High School 2, Surabaya. The lifestyle of the pupils is positive and not significant. There is a negative and non-significant influence of economic literacy on the consumptive behavior of students of the X class of Muhammadiyah High School 2 Surabaya. The results of this study also show that economic literature does not play a role in mediating family economic education, lifestyle, and social media addiction to the consumtive behaviour of students.